Production of green diesel from waste cooking oil via catalytic deoxygenation reaction using metal doped eggshell catalyst - Lee Z.S.; Seah C.C.; Habib S.H.; Hafriz R.S.R.M.; Razali N.M. (Institute of Physics, 2025)
Green diesel production via catalytic deoxygenation of waste cooking oil (WCO) over metal doped eggshell catalyst was investigated in this work. The catalyst was prepared through liquid-liquid precipitation of 5 transition metal solutions and ground eggshell (ES) as the catalyst support. The prepared catalyst, Fe-ES, Cu-ES, Co-ES, Zn-ES, and Ni-ES were characterized using BET surface area and Scanning Electron Microscopy (SEM) analysis. BET surface area data and SEM images of the catalyst shows a promising catalyst physical properties that tailor to the deoxygenation reaction. Gas Chromatography Mass Spectrometry (GCMS) was used to determine the hydrocarbon composition of the oil yield product from the reaction. The reaction also produces gas, soap and liquid acid phase while the remaining unreacted WCO becomes coke. The percentage of all products and coke were calculated using mass balance. Deoxygenation of WCO with Ni-ES catalyst produced highest oil yield at 61.6% with the hydrocarbon content of 56.11%. Ni-ES also produced 22.9% coke; the least percentage compared to other catalyst. The findings proved that Ni-ES catalyst exhibited the highest conversion of WCO into gas and liquid product with a greater yield of oil and minimal coke formation. These findings demonstrate the feasibility and practicality of using eggshell catalysts as substitutes for commercial catalysts in green diesel production. ? Published under licence by IOP Publishing Ltd.